Kelas Ibu Hamil : Teman Setia Menuju Persalinan Bahagia - Apriliana Pipin; Telly Katharina; Intanwati Intanwati; Trivina Trivina; Agnes Dwiana Widi Astuti (BADAN PENERBIT STIEPARI PRESS, 2025)
A common problem faced by the community is the low level of knowledge among pregnant women regarding the importance of regular prenatal checkups, balanced nutrition, prenatal exercise techniques, mental preparation, and warning signs during pregnancy. This condition can increase the risk of complications that endanger the mother and fetus. To address this issue, the